Determinants of Immunity to Measles in Children: A Cross-sectional Study in Northeast Nigeria - Halima Abubakar Ibrahim; Lawan Bukar Maryah; Ibrahim Sanusi Mohammed; Adamu Ibrahim Rabasa (Nigerian Journal of Medicine)
Background: Measles is the most prevalent and leading cause of death among Vaccine-preventable diseases. Nigeria has one of the highest burdens of measles. This study aimed to determine some of the factors associated with the development of protective levels of measles antibodies. Materials and Methods: This Cross-sectional study consisted of 229 children who presented to the Paediatric Outpatient Department of the University of Maiduguri Teaching Hospital. They all had Measles immunoglobulin G assay and screening for HIV infection. Results: Two hundred and Twenty-nine children aged 1–5 years, with a mean (standard deviation) age of 2.05 (1.33) years, and M:F of 1.2:1 were studied. Out of the 229 studied, 145 (63.3%) had received the measles vaccine. Overall, 202 (88.2%) had protective measles antibody levels. Significantly more of the vaccinated subjects, 135, had protective antibody levels compared to the unvaccinated subjects, 67 (93.1% vs. 79.8%, χ2 = 10.836, P = 0.013). Vaccinated subjects (odds ratio [OR]: 3.425 (1.487–7.889), P = 0.004), subjects vaccinated at nine months of age (OR: 3.024 (1.313–6.965), P ≤ 0.0001) and those vaccinated in secondary healthcare facilities (OR: 1.100 (1.000–1.400), P ≤ 0.0001) were more likely to be protected; whereas, severely malnourished subjects were unprotected (OR: 0.189 (0.074–0.481), P ≤ 0.0001). Conclusion: Although this study observed low immunisation coverage (63.3%), most of the subjects studied had protective immunoglobulin G antibodies. Recommendations: Parents should be encouraged to get their children vaccinated against measles and infant and young child feeding practices should be reinforced in all immunisation clinics.